2023
DOI: 10.3389/fimmu.2023.1239142
|View full text |Cite
|
Sign up to set email alerts
|

cGAS-STING signaling pathway in intestinal homeostasis and diseases

Yuchen Yang,
Li Wang,
Ivonne Peugnet-González
et al.

Abstract: The intestinal mucosa is constantly exposed to commensal microbes, opportunistic pathogens, toxins, luminal components and other environmental stimuli. The intestinal mucosa consists of multiple differentiated cellular and extracellular components that form a critical barrier, but is also equipped for efficient absorption of nutrients. Combination of genetic susceptibility and environmental factors are known as critical components involved in the pathogenesis of intestinal diseases. The innate immune system pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 230 publications
0
7
0
Order By: Relevance
“…On the one hand, activation of cGAS-STING signaling is associated with the severity of intestinal inflammation. On the other hand, it plays a key role in preventing tumorigenesis and infection 13 . Colorectal cancer (CRC) patients with high STING expression had increased intratumoral CD8 + T cells infiltration and decreased frequency of lymphovascular infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, activation of cGAS-STING signaling is associated with the severity of intestinal inflammation. On the other hand, it plays a key role in preventing tumorigenesis and infection 13 . Colorectal cancer (CRC) patients with high STING expression had increased intratumoral CD8 + T cells infiltration and decreased frequency of lymphovascular infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The latest study shows that the clinical development of inhibitor has begun, and clinical trials are planned to begin 12 . Interestingly, previous study has reported that the cGAS-STING pathway is involved in the pathogenesis, progression, and therapeutic response of UC 13 . The level of STING is increased in the colon of patients with UC 14 .…”
Section: Introductionmentioning
confidence: 99%
“… 44 The activation of IRF3(interferon regulatory factor 3) and its subsequent induction of IFN-I and other Interferon-stimulated genes (ISGs) constitute the most comprehensively understood process governed by the cGAS-STING pathway’s activation. 45 Furthermore, IRF3 activity is also crucial for the induction of numerous other target genes, including those encoding inflammatory cytokines 46 . In the septic state, cGAS becomes activated when the host cell recognizes the pathogen’s DNA, thereby activating STING, which then promotes IFN-I expression through the IRF3 pathway.…”
Section: Inflammatory and Immune Effects Triggered By Activation Of T...mentioning
confidence: 99%
“… 53 , 82 Furthermore, the STING pathway activation is implicated in regulating the intestinal immune response to bacterial infections and inflammation in the context of sepsis-related intestinal mechanical barrier damage. 46 Additionally, some studies suggest that STING pathway activation might influence septic enteric mechanical barrier injury by modulating the stability of the intestinal flora. 83 Erttmann SF et al discovered that the intestinal flora activates the cGAS-STING signaling pathway in the organism’s cytoplasm, maintaining basal systemic IFN-I production levels, as shown through a series of innate immune pathway-deficient mouse models and in vitro cell culture experiments, combined with 16S rDNA and high-throughput transcriptome sequencing.…”
Section: Organ Tissue Damage Caused By Activation Of Cgas-sting Signa...mentioning
confidence: 99%
“…A growing body of research demonstrates the importance of abnormal cGAS signaling in the pathogenesis of various GI diseases. In ulcerative colitis, abnormal activation of cGAS contributes to the dysregulation of intestinal epithelial autophagy, epithelial cell integrity, and innate immune responses ( Ke et al, 2022 ; Yang et al, 2023 ). Meanwhile, in GI cancers, cGAS-mediated pathways have been shown to be both oncogenic and tumor suppressive ( Ke et al, 2022 ; Yang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%